Crystallization and preliminary X-ray analysis of a novel halotolerant feruloyl esterase identified from a soil metagenomic library - Chen, Shang-ke (International Union of Crystallography, 2012)
Feruloyl esterase cleaves the ester linkage formed between ferulic acid and polysaccharides in plant cell walls and thus has wide potential industrial applications. A novel feruloyl esterase (EstF27) identified from a soil metagenomic library was crystallized and a complete data set was collected from a single cooled crystal using an in-house X-ray source. The crystal diffracted to 2.9 Å resolution and belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 94.35, b = 106.19, c = 188.51 Å, α = β = γ = 90.00°. A Matthews coefficient of 2.55 Å(3) Da(−1), with a corresponding solvent content of 51.84%, suggested the presence of ten protein subunits in the asymmetric unit.